« Capitalismes dépendants » d’Europe centrale et orientale : pièges de la dépendance externe et instrumentalisations domestiques - Violaine Delteil (Revue de la Régulation)
At the crossing of International Political Economy and Political Science, the paper offers some analytical insights to consider the logics and dynamics of the “dependent capitalism” model. This model is illuminated by Eastern Europe, more than by Central Europe, the former region being emblematic of cumulative dependencies driven by economic pressures as well as politico-institutional requirements from the EU. Focalizing on the case of Eastern Europe – compared to Central Europe -, the article exposes the domestic foundations of the external dependency, ie. the “Weak State”, the “low cost” competitiveness regime, as well as the domestic actor’s strategies instrumenting the supranational norms in order to discipline local practices (corruption, informality, ect.). At this yard, the failure of the European integration is largely to be found in a EU governance unable to extract the periphery from a dependency trap that nurtures also a profound political crisis.